How Does Mindfulness Matter in Interpersonal Communication with Students at School? - Indra Yana; Burmansah Burmansah; Sidartha Adi Gautama; Susanto Susanto; Rini Kasrah (Universitas Sebelas Maret, 2024)
Abstract: This study aims to determine the Influence of mindfulness on student interpersonal communication in a Tangerang, Banten Province private school. The problems that occur to students are not entirely correct when talking to their friends, ignoring their friends, and having difficulty expressing their feelings when communicating and interacting. Also, communicating is just talking without knowing the truth. This study uses a quantitative approach with a survey method. The population in this study is 140 junior high school students, with a sample of 105 students using the Slovin formula. The research was conducted in one of the Buddhist private schools in the Tangerang area, Banten Province, with junior high school student respondents. This study uses path analysis. The study's results showed a significant favorable influence between mindfulness and interpersonal communication, which illustrates the significant role of mindfulness as the basis for forming students' mindful character and strengthening students' interpersonal communication at school. This research is expected to be a recommendation for schools to develop mindfulness in developing students' character, especially in strengthening their interpersonal communication.